2018
DOI: 10.1007/jhep10(2018)195
|View full text |Cite
|
Sign up to set email alerts
|

An effective black hole remnant via infinite evaporation time due to generalized uncertainty principle

Abstract: We study a form of generalized uncertainty principle (GUP) that leads to vanishing quantum effect, i.e. ∆x∆p ∼ 0, at sufficiently high momenta. We find that such a GUP allows black holes to evaporate completely, however this process takes an infinite amount of time to achieve, resulting in a metastable remnant. We also discuss some connections between the proposed generalized uncertainty principle with other quantum gravity models.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 40 publications
2
43
0
Order By: Relevance
“…(1), we would find that there is no lower bound for black hole mass, so in principle the black hole can evaporate completely. However the final temperature is finite and nonzero [14,15], also see Fig. (1).…”
Section: Introduction: the Issue With Temperature Of Black Hole Rementioning
confidence: 84%
See 3 more Smart Citations
“…(1), we would find that there is no lower bound for black hole mass, so in principle the black hole can evaporate completely. However the final temperature is finite and nonzero [14,15], also see Fig. (1).…”
Section: Introduction: the Issue With Temperature Of Black Hole Rementioning
confidence: 84%
“…This is the case for the GUP-corrected black hole in [15] with negative GUP parameter α, since r h = 2M , the same as the usual Schwarzschild black hole; c.f. Eq.(4).…”
Section: Proof Of the Theoremmentioning
confidence: 92%
See 2 more Smart Citations
“…For a review of GUP, see [47]. GUP is one of the simplest models of effective quantum gravity, and many interesting results in the study of black hole physics have been produced [48][49][50][51][52][53][54][55][56][57][58][59]. Specifically, the authors of [60] discussed the effect of quantum gravity on the weak cosmic censorship conjecture and showed that the second law of thermodynamics and the cosmic censorship conjecture are violated owing to the rainbow effect.…”
Section: Introductionmentioning
confidence: 99%